Correlation of Adenoid Hypertrophy on Nasoendoscopy and Audiological Parameters in Children (KYAMC Journal, 2021)
Background: Hypertrophy of the adenoid is a common finding in children under 12 years of age, which commonly leads to impairment of hearing.Nasoendoscopyand audiological tests are frequently included in the workup of these patients.Objectives:Aim for this study was to find out whether any correlation exists between the size of adenoids on nasoendoscopy and the audiological parameters.Materials & Methods: This is cross-sectional study conducted from Jan 2019 to Jan 2020 in Khwaja Yunus Ali Medical College Hospital, Enayetpur, Shirajganj. Total 50 patients were included in this study. In all patients, Flexible nasoendoscopy, Pure tone audiometry and Tympanometry was done. Findings were evaluated to assess the correlation of degree of adenoid hypertrophy to the severity of hearing impairment.Results: In this study, mean age of participants was 7.46 (3.62) years. Findings of hypertrophy were – Grade I 7(13%), Grade II 24(47%), Grade III 14(28%), Grade IV 6(12%).Findings of hearing status were – upto 25 dB 14(28%), Between 26–40 dB 32(64%), Above 40 dB 4(8%). Mean hearing loss according to adenoid hypertrophy were – Grade I –19.42dB, Grade II –30.41dB, Grade III – 35.64dB, Grade IV – 38.60dB. Type B curve percentage on adenoid groups were – Grade I – 3(43%), Grade II – 16(67%), Grade III – 11(79%), Grade IV – 6(100%).Conclusion: Adenoid hypertrophy as seen on nasoendoscopy correlates well with the expected audiological parameters in children.KYAMC Journal.2021;12(01): 18-21